New hydrogen-bonded comblike polyimides with mesogenic side chains for stable orientation and fast switching of liquid crystals. Issue 5 (8th April 2020) - Kim, Chunho; Son, Intae; Kim, Jae Hong; Yoo, Ji Yong; Lee, Byungsun; Lee, Jun Hyup
ABSTRACT: New supramolecular comblike polyimides with mesogenic side chains for stable homeotropic orientation and fast electro-optical switching of liquid crystals (LCs) have been prepared through selective intermolecular hydrogen bonding between 4-(4-heptylphenyl)benzoic acid (4HPB) and host polyimide. A low concentration of 4HPB as the mesogenic guest molecule was hydrogen-bonded to polyimide backbone leading to the self-assembled comblike polyimide with enhanced homeotropic orientation properties. The electro-optical characteristics of the LC device containing hydrogen-bonded comblike polyimide exhibited better performance than those of LC cell with conventional polyimide. Because the conventional covalent approach for preparation of polyimides requires considerable synthetic efforts to achieve new functionality in polyimide materials, the proposed noncovalent method is a simple one and highly cost effective. Our controlled methodology should find wide application for the fabrication of functional alignment materials requiring high orientation ability. Graphical Abstract: